Compare the Forms of ACE Gene According to Maximum Oxygen Consumption before and After the Lactic Voltage in 1500 Meters Running Players - Alia Abdulkhader Safah (Journal of Global Pharma Technology, 2016)
The objective of the study was to identify the forms of ACE gene in mid-distance runners as well as to identify maximum oxygen consumption and the pre-voltage and post-voltage lactation threshold of 1500 meters and to determine the differences between the groups according to the two periods before and after the voltage according to the forms of the ACE gene. The research problem was to identify which alleles of the ACE gene were better in the physiological abilities of the players and included the imposition of research. There were differences in the maximum oxygen consumption and the lactic threshold in the two stages before and after voltage according to the gene shapes of 1500 meters running athletes. The researcher used the descriptive method in the survey method. The sample was randomly selected. They were players of Al-Qadisiyah clubs for the field and field players. The sample consisted of 16 players. The sample divided three groups according to the forms of the gene (II, ID, DD). The researcher concluded that the preferred form is the genetic makeup (II), which gives the physiological potential of players running 1500 meters.Keywords: ACE gene, Maximum oxygen consumption and lactic threshold.